Pengaruh Pengetahuan Kewirausahaan dan Efikasi Diri Terhadap Minat Wirausaha Mahasiswa Universitas Serambi Mekkah Kota Banda Aceh - Ijal Fahmi; Yenni Agustina; TM Zulfikar; Jalaluddin; Zakaria (Jurnal EMT KITA, 2023)
This study aims to determine the effect of entrepreneurial knowledge and motivational self-efficacy on entrepreneurial interest in students of the Faculty of Economics, Serambi Mekkah University, Banda Aceh City. The population in this study were all students of the Faculty of Economics with a sample of 30 students. The method used is a survey method with a qualitative descriptive approach. The analytical tool uses multiple regression analysis, the coefficient of determination, and hypothesis testing for partial uses the t test while for the simultaneous use of the F test. The results show that entrepreneurial knowledge and self-efficacy have a positive and significant effect on the interest in entrepreneurship of students of the Faculty of Economics, Serambi Mekkah University, Banda Aceh City. The positive influence of entrepreneurship knowledge and efficacy on entrepreneurial interest shows that knowledge and understanding as well as a person's self-confidence in his ability to carry out entrepreneurial activities greatly influences the person's interest in entrepreneurship. Conversely, if the understanding and belief in one's abilities is low, then the interest in entrepreneurship will also be low.